Heat stress in domestic dogs: morphological and environmental risk factors for dog welfare in a warming world - Nascimento, Pavlos Vinicius do; Veríssimo, Tarsys Noan da Silva; Soares, Wylke Alves de Azevedo; Maia, Maria Isabelly Leite; Carvalho, Lucas Rannier Ribeiro Antonino; Saraiva, Edilson Paes (Frontiers in Animal Science, 2025)
Global temperature rise increasingly exposes domestic dogs (Canis lupus familiaris) to thermal challenges, especially in tropical and urban regions where climate change, artificial structures, and inadequate care converge. Despite the species’ adaptive capacity, morphological traits such as dense coats, brachycephalic conformation, and obesity reduce thermoregulatory efficiency, heightening the risk of heat stress. This review synthesizes evidence on physiological heat exchange mechanisms, discusses subclinical indicators of thermal overload, and presents preventive management strategies tailored to breed profiles and environmental contexts. Emerging technologies, such as wearable thermal sensors, and educational actions targeting caregivers and professionals are explored as tools to promote adaptive care. By adopting a One Welfare perspective, the article connects animal welfare, public health, and sustainability, contributing to professional, policy, and educational practices aimed at protecting dogs from thermal stress in a warming world.